Interplay of Electronic and Steric Effects to Yield Low‐Temperature CO Oxidation at Metal Single Sites in Defect‐Engineered HKUST‐1. Issue 26 (17th April 2020) - Wang, Weijia; Sharapa, Dmitry I.; Chandresh, Abhinav; Nefedov, Alexei; Heißler, Stefan; Heinke, Lars; Studt, Felix; Wang, Yuemin; Wöll, Christof
Abstract: In contrast to catalytically active metal single atoms deposited on oxide nanoparticles, the crystalline nature of metal‐organic frameworks (MOFs) allows for a thorough characterization of reaction mechanisms. Using defect‐free HKUST‐1 MOF thin films, we demonstrate that Cu + /Cu 2+ dimer defects, created in a controlled fashion by reducing the pristine Cu 2+ /Cu 2+ pairs of the intact framework, account for the high catalytic activity in low‐temperature CO oxidation. Combining advanced IR spectroscopy and density functional theory we propose a new reaction mechanism where the key intermediate is an uncharged O2 species, weakly bound to Cu + /Cu 2+ . Our results reveal a complex interplay between electronic and steric effects at defect sites in MOFs and provide important guidelines for tailoring and exploiting the catalytic activity of single metal atom sites. Abstract : A complex interplay : A thorough study combining advanced spectroscopy and theory reveals that electronic and steric effects occur at reduced Cu + /Cu 2+ single dimers in defect‐engineered HKUST‐1 SURMOF to yield high catalytic activity for low‐temperature CO oxidation. A new reaction mechanism is presented involving an uncharged O2 species as the key intermediate.